2020
DOI: 10.34011/juriskesbdg.v12i1.869
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Edukasi Terhadap Efektivitas Konsumsi Tablet Fe Dan Kadar Hb Pada Ibu Hamil

Abstract: Anemia mempunyai efek negatif terhadap pertumbuhan dan perkembangan janin. Anemia dapat menyebabkan penyulit dalam kehamilan, persalinan, bahkan kematian ibu dan anak. Konsumsi tablet Fe memberikan efek positif terhadap peningkatan kadar hemoglobin. Tujuan penelitian ini untuk menganalisis pengaruh edukasi terhadap efektivitas konsumsi tablet Fe dan kadar Hb pada ibu hamil. Metode yang digunakan quasi eksperimental, rancangan non-equivalent-control group design. Subjek penelitian terdiri dari 22 orang kelompok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Stunting: Mother's characteristics also need to be considered because stunting is a chronic condition that arises as a result of long-term factors such as poverty, inappropriate parenting due to busy parents, poor maternal knowledge about nutrition due to low maternal education, and recurrent illnesses due to poor hygiene and sanitation (Ekayanthi & Purnamasari, 2020). Characteristics such as the mother's education level, age, and others are crucial considerations.…”
Section: Resultsmentioning
confidence: 99%
“…Stunting: Mother's characteristics also need to be considered because stunting is a chronic condition that arises as a result of long-term factors such as poverty, inappropriate parenting due to busy parents, poor maternal knowledge about nutrition due to low maternal education, and recurrent illnesses due to poor hygiene and sanitation (Ekayanthi & Purnamasari, 2020). Characteristics such as the mother's education level, age, and others are crucial considerations.…”
Section: Resultsmentioning
confidence: 99%
“…Research showed that behavior change which caused by the knowledge improvement will last longer than behavior without knowledge improvement Donsu, 2017;Saadah, Suparji and Sulikah, 2020). In addition, research by shows that there was an effect of education on adherence to taking iron tablets and increasing Hb levels in pregnant women (Ekayanthi and Purnamasari, 2020), this statement explains that knowledge may be important on improving adherence of iron supplement consumption.…”
Section: Methodsmentioning
confidence: 96%
“…Adapun manfaat PHBS di Rumah Tangga : Selanjutnya akan dipahami dengan kemampuan orang tersebut menginterprestasikan objek yang diketahuinya tersebut secara benar, selanjutnya diaplikasikan, dianalisis sehingga orang tersebut memiliki kemampuan membuat kesimpulan yang logis dari komponen-komponen pengetahuan yang dimilikinya. Hal ini sering disebut sintesis, yang akhirnya orang tersebut mampu untuk melakukan evaluasi suatu objek yang diamati dengan melakukan pembenaran atau penilaian (Ekayanthi & Purnamasari, 2020).…”
Section: Pengetahuanunclassified